ChemInform Abstract: Oxidative Etching for Controlled Synthesis of Metal Nanocrystals: Atomic Addition and Subtraction. Issue 46 (18th November 2014) - Long, Ran; Zhou, Shan; Wiley, Benjamin J.; Xiong, Yujie
Abstract Review: 152 refs.